Standby thermal model of a vanadium redox flow battery stack with crossover and shunt-current effects. (15th April 2019) - Trovò, Andrea; Marini, Giacomo; Sutto, Alessandro; Alotto, Piergiorgio; Giomo, Monica; Moro, Federico; Guarnieri, Massimo
Graphical abstract: Highlights: A new model for studying the thermal standby behavior of a VRFB stack is presented. Losses from species crossover and shunt currents are duly taken into account. The dynamic cell temperature distribution in the stack is computed. Successful validation against data from a 9 kW experimental stack is described. Simulations show that shunt currents can have pivotal effects in high-power stacks. Abstract: This paper presents an original model capable of simulating the thermal behavior of a vanadium redox flow battery stack in standby condition, i.e. without power and reactant flow, where the temperature distribution in the cells evolves because of ions crossover through the membrane, Joule losses due to shunt currents and inherent self-discharge effects. For the first time, a model is presented that is capable of simulating the cell temperature distribution in the stack and its time evolution considering all above effects. The model is applied to a 9 kW/40-cell stack and validated against measurements from a thermal imager. Numerical results show that shunt currents affect the temperature in the stack and can be responsible for local increases of cell temperatures up to 10 °C if the solutions are initially at high state of charge. This effect can be critical if standby occurs after a period of operation, with the electrolyte stack temperature markedly higher than air temperature. In addition, results show that shunt currents can play a major role in the thermal behavior of compact stacks, based on new materials capable of high power density and low ion crossover. The model presented here can constitute the basis for advanced cooling strategies.